Gonadotropin-releasing hormone and growth hormone act as anti-inflammatory factors improving sensory recovery in female rats with thoracic spinal cord injury - Martínez-Moreno, Carlos Guillermo; Calderón-Vallejo, Denisse; Díaz-Galindo, Carmen; Hernández-Jasso, Irma; Olivares-Hernández, Juan David; Ávila-Mendoza, José; Epardo, David; Balderas-Márquez, Jerusa Elienai; Urban-Sosa, Valeria Alejandra; Baltazar-Lara, Rosario; Carranza, Martha; Luna, Maricela; et al. (Frontiers in Neuroscience, 2023)
The potential for novel applications of classical hormones, such as growth hormone (GH) and gonadotropin-releasing hormone (GnRH), is based on their demonstrated neurotrophic effects in both in vitro and in vivo experimental models, as well as in a growing number of clinical trials. The aim of this study was to investigate the effects of chronic administration of GnRH and/or GH on the expression of several proinflammatory and glial activity markers in damaged neural tissues, as well as on sensory recovery, in animals submitted to thoracic spinal cord injury (SCI). Additionally, the effect of a combined GnRH + GH treatment was examined in comparison to single hormone administration. Spinal cord damage was induced by compression using catheter insufflation at thoracic vertebrae 10 (T10), resulting in significant motor and sensory deficits in the hindlimbs. Our results indicate that a chronic treatment (3-5 week) with GH and/or GnRH significantly reduced the expression of proinflammatory (IL6, IL1B and iNOS) and glial activity (Iba1, CD86, CD206, and vimentin) markers in the spinal cord tissue, and improved sensory recovery in the lesioned animals. Furthermore, we found that the caudal section of the spinal cord was particularly responsive to GnRH or GH treatment, as well as to their combination. These findings provide evidence of an anti-inflammatory and glial-modulatory effect of GnRH and GH in an experimental model of SCI and suggest that these hormones can modulate the response of microglia, astrocytes, and infiltrated immune cells in the spinal cord tissue following injury.